Education of pregnant women to increase mothers' knowledge and attitudes regarding exclusive breastfeeding - A Syamsinar Asmi; Trimaya Cahya Mulat (Edukasi Ilmiah Indonesia, 2024)
Exclusive breastfeeding (ASI-E) is a very important practice for the optimal health and development of the baby. However, the knowledge and attitudes of pregnant women towards breast milk often require improvement. This study aims to investigate the effectiveness of education programs for pregnant women in increasing their knowledge and attitudes regarding breastfeeding. There was a significant improvement in the knowledge and attitudes of pregnant women who participated in the education program compared to the control group. Post-intervention, pregnant women in the intervention group had a better understanding of the benefits of breast milk-E, correct breastfeeding techniques, and resolution of problems that may arise during the breastfeeding period. Positive attitudes toward ASI-E were also more dominant among the intervention group. This educational program provides strong evidence that increasing the knowledge and attitudes of pregnant women through educational interventions can be an effective strategy to improve breastfeeding practices. Future recommendations include long-term research to evaluate the long-term impact of these education programs on breastfeeding practices as well as the inclusion of fathers in education efforts.